Electrically small complementary split‐ring resonator antenna on eighth‐mode substrate integrated waveguide. Issue 8 (1st April 2013) - Sam, S.; Lim, S.
Abstract : An electrically small substrate integrated waveguide (SIW) antenna is proposed at 5.22 GHz. Its electrical size is reduced by a complementary split‐ring resonator which is loaded on the eighth‐mode SIW (EMSIW). The EMSIW occupies only 12.5% of the conventional SIW with the same dominant resonant frequency. The S‐parameters and radiation patterns are investigated by full‐wave simulation and measurements. Results show the omnidirectional radiation pattern with a 4 dBi peak gain.